2000
DOI: 10.2307/3802977
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Day Roosts by Red Bats in Mixed Mesophytic Forests

Abstract: YOUNG, H. 1963. Age-specific mortality in the eggs and nestlings of blackbirds. Auk 80:145-155. ZIMMERMAN, J. L. 1984. Nest predation and its relationship to habitat and nest density in dickcissels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
5
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 36 publications
9
76
5
3
Order By: Relevance
“…The difference in canopy closure observed between roost trees of northern bats (Myotis septentrionalis), which select higher closure (Foster and Kurta, 1999;Lacki and Schwierjohann, 2001), and M. sodalis, which select more open canopies (Callahan et al, 1997;Foster and Kurta, 1999), is a case in point. In turn, habitat characteristics important to foliageroosting species, such as the lasiurine bats (e.g., Menzel et al, 1998;Hutchinson and Lacki, 2000), cannot be expected to mimic those required of snag or cavity-roosting bats (Hayes, In press).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in canopy closure observed between roost trees of northern bats (Myotis septentrionalis), which select higher closure (Foster and Kurta, 1999;Lacki and Schwierjohann, 2001), and M. sodalis, which select more open canopies (Callahan et al, 1997;Foster and Kurta, 1999), is a case in point. In turn, habitat characteristics important to foliageroosting species, such as the lasiurine bats (e.g., Menzel et al, 1998;Hutchinson and Lacki, 2000), cannot be expected to mimic those required of snag or cavity-roosting bats (Hayes, In press).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we identified 25 published studies that met desired habitat comparison requirements, and were used in calculating power analyses. These include (in alphabetical order): Barclay et al (1988), Betts (1996Betts ( , 1998, Boonman (2000), Brigham et al (1997), Callahan et al (1997), Campbell et al (1996), Crampton and Barclay (1998), Cryan et al (2001), Foster and Kurta (1999), Grindal (1999), Hutchinson and Lacki (2000), Lacki and Schwierjohann (2001), Lunney et al (1995), Mattson et al (1996), Menzel et al (1998), Ormsbee and McComb (1998), Rabe et al (1998), Sasse and Pekins (1996), O'Donnell (1999a, 1999b), Vonhof (1996), Vonhof and Barclay (1996), Waldien et al (2000), and Weller and Zabel (2001). For each paper we determined the number of habitat characteristics quantified, number of habitat characteristics found to be significant, whether nominal (i.e., categorical) habitat characteristics were examined, and whether habitat characteristics were tested using a multivariate approach, tested separately, or both.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, bats may avoid some predators by roosting high enough above the ground (Riskin and Pybus, 1998;Hutchinson and Lacki, 2000), in narrow crevices (Vonhof and Barclay, 1997;Riskin and Pybus, 1998) or in darker parts of the roost where visually oriented predators cannot operate (Riskin and Pybus, 1998). As long as such primary defences suffice to minimise the accessibility of roosting spots, bats might ignore predator olfactory cues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, long-legged myotis, Myotis volans, in the northwestern USA switch between riparian bottoms and upper-slope positions during pregnancy, but select roosts in upper-slope positions during lactation, where they would be exposed to greater solar radiation (Baker and Lacki 2006). Studies of bats in south-eastern forests of North America have also observed preferences for roosting in upper-slope positions by foliage-roosting eastern red bat, Lasiurus borealis, and bark-and cavity-roosting bats (Myotis and Eptesicus) (Hutchinson and Lacki 2000;Lacki and Schwierjohann 2001;, suggesting that higher slopes are important for roost selection in some forest bat species in both eastern and western parts of North America and should be accounted for in forest planning. Use of lower slope positions and riparian corridors for roosting is common in several bats in eastern and south-eastern forests, however, including bark-and cavity-roosting (Watrous et al 2006;Fleming et al 2013) and foliage-roosting species Hein et al 2008b;O'Keefe et al 2009).…”
Section: Slope and Aspectmentioning
confidence: 99%